Effect of Home Postpartum Care on Quality of Life of Low Risk Mothers - ST Mirmolaei; M Amelvalizadeh; M Mahmoudi; Z Tavakol (Tehran University of Medical Sciences, 2011)
Background & Aim: Home care visits have unique advantages in many social problems and health complications such as psychologic complications and adverse birth outcomes. The aim of this study was to identify the effect of postpartum care at home on quality of life among low risk mothers. Methods & Materials: This interventional study was conducted in Akbarabad health center of Tehran University of Medical Sciences in 2010. A total of 200 mothers were randomly allocated in two intervention and control groups. Mothers in the control group received two post partum visits in health care center and the intervention group received care at home. Data were collected through a questionnaire including demographic characteristics and the mothers&apos quality of life items along with a growth and development monitoring chart for newborns. For analyzing data, Mann-Withney U, Wilcoxon and Chi-square tests were used. Results: Most of the mothers aged 20-29 years old. The number of visits were statistically different between the two groups (P=0.00, P=0.01). Dimensions of quality of life in the two groups were not statistically different: (Physical dimension: P=0.052), (Emotional dimension: P=0.775), (Public health dimension: P=0.068), (Social performance dimension: P=0.780) and (Total score: P=0.213). Conclusion: the results of our study did not show no positive improvements in home postpartum care in comparison with the health care centers care. More studies are recommended.